Video-assisted thoracoscopic lobectomy versus stereotactic radiotherapy for stage I lung cancer - Aragón, Javier; Perez, Itzell; Gonzalez-Rivas, Diego (Journal of Thoracic Disease, 2015)
With great interest we read the study of Hamaji et al. (1) entitled “Video-Assisted Thoracoscopic lobectomy Versus Stereotactic Radiotherapy for Stage I Lung Cancer” which was recently published in Annals of Thoracic Surgery. With a mean follow-up of 48 months, the authors show that lobectomy performed by video-assisted thoracoscopic surgery (VATS) offers better results than stereotactic radiotherapy (SBRT) in the treatment of patients with pathologically proved non-small cell lung cancer (NSCLC) in early stages.